Mortality Rates After Paclitaxel-Coated Device Use in Patients With Occlusive Femoropopliteal Disease: An Updated Systematic Review and Meta-Analysis of Randomized Controlled Trials. (October 2021) - Dinh, Krystal; Limmer, Alexandra M.; Chen, Andy Z. L.; Thomas, Shannon D.; Holden, Andrew; Schneider, Peter A.; Varcoe, Ramon L.
Purpose: A late increased mortality risk has been reported in a summary level meta-analysis of patients with femoropopliteal artery occlusive disease treated with paclitaxel-coated angioplasty balloons and stents. However, at the longer follow up timepoints that analysis was limited by small trial numbers and few participants. The aim of this study was to report an updated summary level risk of all-cause mortality after treatment with paclitaxel-coated devices in that same patient group. Materials and Methods: We performed a systematic review and meta-analysis of randomized controlled trials to investigate the mortality outcomes associated with paclitaxel-coated devices used to treat patients with occlusive disease of femoropopliteal arteries (last search date December 10, 2020). The single primary endpoint was all-cause mortality. Results: We identified 34 randomized controlled trials (7654 patients; 84% intermittent claudication). There were 622 deaths among 4147 (15.0%) subjects in the paclitaxel device group and 475 deaths among 3507 (13.5%) subjects in the noncoated control group [relative risk ratio (RR) 1.07, 95% confidence interval (CI) 0.96 to 1.20, p=0.20, I 2 =0%). All-cause mortality was similar between groups at 12 months (34 studies, 7654 patients; RR 0.99, 95% CI 0.81 to 1.22, p=0.94, I 2 =0%), 24 months (20 studies, 3799 patients; RR 1.16, 95% CI 0.87 to 1.55, p=0.31, I 2 =0%), and 60 months (9 studies, 2288 patients; RR 1.19, 95% CI 0.98 to 1.45, p=0.08, I 2 =0%). Conclusion: This updated meta-analysis with included additional trials and larger patient numbers shows no evidence of increased risk of all-cause mortality in patients treated with paclitaxel-coated devices, compared with uncoated devices for femoropopliteal disease at all time points to 60 months. There is therefore no justification to limit their use, or alter regulatory body follow-up recommendations in this patient population. Systematic Review Registration: CRD42020216140.